System requirements engineering : a SysML supported requirements engineering method - Bron, Jean-Yves (ISTE, Ltd. ; Wiley, 2020)
The book deals with requirements engineering in the context of System Engineering. He proposes a method to guide this activity engineering. The method is supported by the SysML modeling language. A first chapter aims to present the context and the associated definitions, to position the requirements engineering in the processes system engineering, to define the modeling and its contributions, and to make the link with the management of IS projects. The second chapter is devoted to the proposed method for implementing the requirements engineering subprocesses. Each of the 8 activities the component is first described before specifying how the SysML language can be exploited to achieve it effectively. The 3rd chapter is an application of the method to define the needs of the stakeholders of a system. The example is built on the basis of the RobAFIS'2018 competition. The 4th chapter continues the application of the method in the continuity of the IS processes to define the requirements of the same system.